Multifunctional Nanomaterials for Ferroptotic Cancer Therapy - Shi, Zhiyuan; Zheng, Jianzhong; Tang, Wenbin; Bai, Yang; Zhang, Lei; Xuan, Zuodong; Sun, Huimin; Shao, Chen (Frontiers in Chemistry, 2022)
Patient outcomes from current clinical cancer therapy remain still far from satisfactory. However, in recent years, several biomedical discoveries and nanotechnological innovations have been made, so there is impetus to combine these with conventional treatments to improve patient experience and disease prognosis. Ferroptosis, a term first coined in 2012, is an iron-dependent regulated cell death based on the production of reactive oxygen species (ROS) and the consequent oxidization of polyunsaturated fatty acids (PUFAs). Many nanomaterials that can induce ferroptosis have been explored for applications in cancer therapy. In this review, we summarize recent developments in ferroptosis-based nanomaterials for cancer therapy and discuss the future of ferroptosis, nanomedicine, and cancer therapy.